Implementasi Manajemen Berbasis Sekolah Sebagai Strategi Pemberdayaan dan Penguatan Pendidikan Karakter SDN 1 Citalang Kecamatan Purwakarta - Aris Purwadin; Atik Kurniawati; Iin Sinta; Alwin Mujaiyanah; Nita Nurbaeti; Nisa Lutfi; Faiz Karim Fatkhullah (Indra Institute Research & Publication, 2026)
This study aims to describe and analyze the implementation of School Based Management (SBM) at SDN 1 Citalang as a strategy for empowerment and character education strengthening. Using a qualitative approach with a case study design, data were collected through in depth interviews with the principal and a teacher, participant observation, and documentation studies. Data analysis followed Miles and Huberman's interactive model involving data reduction, display, and conclusion drawing. Findings reveal that SBM implementation has been effectively executed through the integration of culturally grounded character programs, particularly the